Optimization of Robusta Ground Coffee Raw Material Inventory Using the MRP Method with Monte Carlo Simulation (Case Study of CV Kopi Citarasa Persada): Optimasi Persediaan Bahan Baku Kopi Bubuk Robusta Menggunakan Metode MRP dengan Simulasi Monte Carlo (Studi Kasus CV Kopi Citarasa Persada) - Fitria Ayu Novitasari; Sri Tjondro Winarno; Dita Atasa (Jurnal Ilmiah Sosio Agribis, 2026)
The production process is a key activity in the agro-industry that determines the company's success in meeting market demand efficiently. CV Kopi Citarasa Persada is a robusta ground coffee processing company that faces problems in controlling raw material inventory in the form of dried coffee beans, labels, and stand-up pouches  which impacts high inventory costs and the risk of raw material shortages. This study aims to project the demand for robusta ground coffee in 2026 and plan raw material inventory with minimal inventory costs. The method used is Monte Carlo simulation forecasting and lot sizing techniques in MRP, namely Lot For Lot (LFL) and Fixed Period Requirement (FPR). The results show that the projected demand for robusta ground coffee in 2026 is 1,821 kg with Monte Carlo simulation validation resulting in a MAPE of 16.15%, including the good category. The results of MRP for 48 weekly periods and produce raw material requirements in the form of 3,642 kg of dried coffee beans, 1,821 pcs labels, and 1,821 pcs stand-up pouches . The LFL technique resulted in 48 ordering frequencies with a total inventory cost of Rp764,050 for dried coffee beans and Rp815,752 for labels and stand-up pouches . Meanwhile, the FPR technique resulted in 10 ordering frequencies with a total inventory cost of Rp278,833 for dried coffee beans and Rp289,532 for labels and stand-up pouches . The FPR technique is the best alternative method because it is able to minimize total inventory costs.